1994
DOI: 10.1093/fampra/11.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Experiences of Health Checks in General Practice: a Sample Survey

Abstract: The 1990 contract for general practitioners in the UK offered incentives for them to organize health promotion clinics and required them to perform 'lifestyle' checkups of their patients every 3 years, despite uncertainty about the impact of such checks on patient health. To address this lack of appropriate evaluation, a follow-up study to assess benefits in terms of patient behaviour and health resulting from the introduction of lifestyle checkups in general practice in a sample of more than 7000 patients age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
1
0
3
Order By: Relevance
“…37,38 However in eight studies education was neither a facilitator nor a barrier. 19,20,[39][40][41][42][43][44] Overall, low SES was reported to be both a barrier and a facilitator, 45,46 and higher SES to be a facilitator. 47 In total, 18 studies (46%) reported about age, of which 12 (67%) reported it as a barrier or facilitator.…”
Section: Barriers and Facilitatorsmentioning
confidence: 99%
“…37,38 However in eight studies education was neither a facilitator nor a barrier. 19,20,[39][40][41][42][43][44] Overall, low SES was reported to be both a barrier and a facilitator, 45,46 and higher SES to be a facilitator. 47 In total, 18 studies (46%) reported about age, of which 12 (67%) reported it as a barrier or facilitator.…”
Section: Barriers and Facilitatorsmentioning
confidence: 99%
“…Mange undersøgelser beskaeftiger sig med inviterede, der undlader at lade sig screene -men mest omkring hvilke organisatoriske tiltag, der vil kunne få så mange som muligt til at deltage og ofte med fokus på social ulighed (14)(15)(16). Kun få har beskaeftiget sig mere udførligt med enkeltindividets bagvedliggende begrundelse for at sige nej tak til at lade sig screene eller til blot at udeblive (17,18).…”
Section: Screening Som Forebyggelsesstradegiunclassified
“…Her bruges mål som selvvurderet risiko eller helbred, General Health Questionnaires, livskvalitetsmål, et spørgeskema med få svarmuligheder eller få åbne spørgsmål som resultatmål til at beskrive, hvordan helbredsundersøgelser påvirker den screenede gruppe (17,18,45,65,101,102,(141)(142)(143)(144)(145)147).…”
Section: Den Praktiserende Laege -Mellem Barken Og Veden?unclassified
See 1 more Smart Citation